A Case Study Of Supply Chain Management Practices In Lafarge Malayan Cement Berhad - Murugiah, Sitambaram (2004)
This thesis aims to evaluate the current state of Supply Chain Management in Lafarge Malayan Cement Bhd (LMCB), in order to produce realistic recommendations to improve its efficiency.